Tinjauan masalah sebelum dan setelah pandemi: Analisis klinik akuntansi di Badan Pengelolaan Keuangan Aset Daerah Jawa Timur - Mustarsida, Adinda (Maliki Interdisciplinary Journal, 2023)
The Covid-19 pandemic has spread almost all over the world, one of which is Indonesia. The occurrence of the Covid-19 pandemic has had quite a severe effect on the people and the government and the Indonesian state. The situation that occurred at the UPT PPK BPKAD East Java Province, their problems narrowed to finances. There were a number of points of complaint about how payment procedures were at that time suddenly changed to online. As we know that the Covid-19 pandemic has limited us to all things. There are several conclusions about the problems that have occurred and have been complained to the UPT PPK BPKAD Consultation Clinic. This problem is actually more about financial management which is starting to have problems. But during the Covid-19 pandemic, the most problematic in terms of damage was financial management. Finding the right solution to stabilize the problem in certain consultations. The visible changes in the types of problems that existed during the Covid-19 pandemic and after the Covid-19 pandemic are able to give us an idea that when the pandemic started in Indonesia, there was a sudden revolution. This change is too fast with regard to finance, where every community is not allowed to have physical contact with strangers.